Combined administration of a sedative dose sevoflurane and 60% oxygen reduces inflammatory responses to sepsis in animals and in human PMBCs - Zhang, Er-Fei (Am J Transl Res, 2017)
Our study aims to investigate the effects of the inhalation of subanesthestic doses of sevoflurane combined with oxygen on sepsis. Male Sprague-Dawley rats or Male ICR/Km mice underwent caecal ligation and puncture (CLP) or intraperitoneal injection of lipopolysccharide (LPS) to induce sepsis, while sham rats were used as control. Then, rats were treated with the inhalation of sevoflurane in oxygen; and air or 100% oxygen was used as control. Seven-day survival, lung injury and inflammatory factors were assessed. In this in vitro experiment, we obtained RAW264.7 macrophages and human peripheral blood mononuclear cells (PBMCs) incubated by LPS or plasma from septic patients to explore the NF-κB pathway in the effect of the inhalation of sevoflurane combined with oxygen in sepsis. In this study, we found that the inhalation of 0.5 MAC of sevoflurane in 60% oxygen was the best protocol for protecting against lethality resulting from sepsis and ALI, and there was a time window for these protective effects. We also founded that 0.5 MAC of sevoflurane in 60% oxygen inhibited the nuclear translocation of NF-κB in human PBMCs induced by LPS or plasma from septic patients. The subanesthesia dose sevoflurane in 60% oxygen may reduce sepsis-induced inflammatory responses in animals and in PBMCs, and the inhibition to the activation of the NF-κB pathway may contribute to this protection.